WORKSHOP ASSESSMENT AS LEARNING BAGI GURU-GURU SDN RUNGKUT MENAGGAL I SURABAYA - Feny Rita, Fiantika; Dian Kusmaharti; Arif Mahya Fanny; Ida Sulistyawati (Universitas PGRI Adi Buana Surabaya, 2025)
This is a Community Service activity carried out by the Community Service TEAM, Elementary School Teacher Education lecturers, Faculty of Education, PGRI Adi Buana University, Surabaya. The aim of this service activity is to increase teacher competence in designing assessment as learning. The participants in this activity were teachers at SDN Dukuh Menanggal I Surabaya. This service activity was carried out on November 13 2024 using presentation, modeling and simulation methods accompanied by assignments. The results of the workshop showed that participants were able to understand and design assessment as learning well, participants were motivated to take part in the assessment as learning development workshop, and there was a change in knowledge/competence in developing learning assessments.